Self-selection and advice in venture capital finance - Christian Keuschnigg; Søren Bo Nielsen (Center for Economic Studies and ifo Institute (CESifo), 2007)
In financing start-up firms, venture capitalists carefully select among alternative projects, design incentive compatible financial contracts and support portfolio companies with value enhancing managerial advice. This paper considers how venture capitalists can induce selfselection among entrepreneurial firms with different qualities by designing appropriate contracts and offering commercial support. We study the efficiency of the competitive market equilibrium with respect to the level and quality of entrepreneurship and the level of effort by entrepreneurs and venture capitalists. We also provide comparative statics results with respect to basic preference and technology parameters.
Keywords: D82; G24; M13; 330; Risikokapital; Unternehmensgründung; Unternehmer; Moral Hazard